A fuzzy logic PI control with feedforward compensation for hydrogen pressure in vehicular fuel cell system. (27th January 2021) - Yuan, Hao; Dai, Haifeng; Wu, Wei; Xie, Jiaping; Shen, Jun; Wei, Xuezhe
Abstract: In a vehicular fuel cell system, alternative load and frequent purge action can lead to anode pressure varies with the hydrogen mass flow fluctuation. It's crucial to control the pressure difference between anode and cathode within a reasonable range to avoid adverse phenomena such as membrane failure, reactant starvation, or even water management fault. In this paper, an improved proportional integrative (PI) controller by the fuzzy logic technique that considers the engineer experience and knowledge on the hydrogen supply system behavior is proposed for hydrogen pressure control, in which the PI parameters are tuned by a fuzzy decision process. Furthermore, load current and purge action regarded as input disturbances are applied for feedforward compensation to reduce the pressure response hysteresis. A hydrogen supply subsystem based on the proportional valve is modeled, and corresponding parameters are determined by analyzing the response time and steady pressure fluctuation. The performance of the conventional PI controller, the fuzzy logic PI (FLPI) controller and fuzzy logic PI with feedforward (FLPIF) controller is validated. The presented results indicated that the FLPI controller significantly improves the dynamic response of hydrogen pressure compared to the PI controller, and the FLPIF controller can further reduce overshoot caused by disturbance. Finally, the proposed FLPIF controller is implemented on a rapid prototype platform of the hydrogen supply subsystem and an actual fuel cell system, exhibiting satisfactory performance. Highlights: A proportional valve controls anode pressure to track cathode pressure. Hydrogen pressure regulation is developed by feedforward fuzzy logic PI controller. The feedforward compensation reduces pressure fluctuations of 0.8 kPa. Pressure fluctuation was within 2 kPa in the test bench and real fuel cell system.